2009
DOI: 10.1016/j.devcel.2009.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog and Bmp Polarize Hematopoietic Stem Cell Emergence in the Zebrafish Dorsal Aorta

Abstract: Summary Haematopoietic stem cells (HSCs) are first detected in the floor of the embryonic dorsal aorta (DA) and here we investigate the signals that induce the HSC programme there. We show that while continued Hedgehog (Hh) signalling from the overlying midline structures maintains the arterial programme characteristic of the DA roof, a ventral Bmp4 signal induces the blood stem cell programme in the DA floor. This patterning of the DA by Hh and Bmp is the mirror image of that in the neural tube, with Hh favou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
141
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(151 citation statements)
references
References 48 publications
(74 reference statements)
8
141
0
1
Order By: Relevance
“…To test this, we used two different but specific BMP type I receptor ALK2/3/6 inhibitors LDN193189 and dorsomorphin (Yu et al, 2008a,b). In agreement with previous studies on BMP signaling (Durand et al, 2007;Wilkinson et al, 2009), 10 µM dorsomorphin significantly reduced the hematopoietic CFUs compared with the control (Fig. 4 C).…”
Section: Prohematopoietic Effect Of Forskolin Is Dependent On Bmp Typsupporting
confidence: 81%
See 1 more Smart Citation
“…To test this, we used two different but specific BMP type I receptor ALK2/3/6 inhibitors LDN193189 and dorsomorphin (Yu et al, 2008a,b). In agreement with previous studies on BMP signaling (Durand et al, 2007;Wilkinson et al, 2009), 10 µM dorsomorphin significantly reduced the hematopoietic CFUs compared with the control (Fig. 4 C).…”
Section: Prohematopoietic Effect Of Forskolin Is Dependent On Bmp Typsupporting
confidence: 81%
“…At the genomic level, the BMP target SMAD1 Bmp4 is a ventral signal arising from the mesenchyme that promotes hematopoietic development. Zebrafish data largely fine-tunes this theory by suggesting that the BMP ligands from the ventral mesenchyme and the pronephros region polarize the dorsal aorta opposed with Hedgehog ligands from the notochord (Wilkinson et al, 2009). In our study, BMP ligands are also found ventrally, but we propose a new source of BMP ligands in the AGM that has been previously underappreciated.…”
Section: Discussionmentioning
confidence: 99%
“…A further subset of MSCs proposed to play a role in supporting BM HSCs are those that express the filament protein Nestin. These Nestin 1 cells are closely [114][115][116] Abbreviations: CSF, colony-stimulating factor; HSC, hematopoietic stem cell; HSPC, hematopoietic stem/progenitor cell; SNS, sympathetic nervous system. [95].…”
Section: Mesenchymal Stem/stromal Cellsmentioning
confidence: 99%
“…Addition of BMP4 ligand increases HSC output from cultured mouse aortagonad-mesonephros (AGM) tissue, and inhibition of BMP signaling by an antagonist ligand gremlin1 suggests that BMP is required for AGM hematopoiesis (19). In zebrafish, BMP signaling is required for the generation of runx1 positive HE and temporal loss of function analysis strongly suggests that the source of BMP is the BMP4 ligand underneath the DA (18). On the other hand, loss of function experiments in mouse embryos and embryoid body (EB) cultures did not reveal a role for BMP signaling after the specification of kdr + mesoderm, which contains all of the precursors of blood and endothelium (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Specifically, BMP4 ligand is expressed in the mesenchyme around the DA across species (16)(17)(18). Addition of BMP4 ligand increases HSC output from cultured mouse aortagonad-mesonephros (AGM) tissue, and inhibition of BMP signaling by an antagonist ligand gremlin1 suggests that BMP is required for AGM hematopoiesis (19).…”
mentioning
confidence: 99%